Chapter 1 Consuming atmospheres A journey through the past, present, and future of atmospheres in marketing - Steadman, Chloe (Taylor & Francis, 2024)
This chapter begins by introducing readers to the inspiration behind the Consuming Atmospheres book. Readers are then taken on a journey through the past, present, and future of the topic of consuming atmospheres in the marketing field, through the three themes organising this edited collection: Part I: Designing Atmospheres, Part II: Experiencing Atmospheres, and Part III: Researching Atmospheres. Within each of these thematic areas, the chapters forming this collection are also introduced, demonstrating how they build upon - and converse with - existing research in this area. The chapter concludes by suggesting several avenues for future work on consuming atmospheres, to inspire future atmospheric investigations in marketing - and beyond.